APPLICATION OF MINERAL TRIOXIDE FILLER IN ENDODONTICS (REVIEW ARTICLE) - Ishniyazova G. B. (Web of Journals Publishing, 2023)
The purpose of this article is to investigate the characteristics of mineral trioxide aggregate (MTA) from a clinical point of view, even in comparison with other biomaterials. All clinical data regarding this dental material will be evaluated in this review article. Data obtained from a review of the literature over the past 10 years identified 19 articles that could address the clinical aspects of MTA. The results obtained in this article are an important step to demonstrate the safety and predictability of oral rehabilitation with these biomaterials and advance the path to improve their properties in the future.
Keywords: dental materials, mineral trioxide aggregate, MTA, Portland cements, dentin, pulp exposure, pulp capping, root canal filling.